Study of Mn4Si7 Silicide Alloys Produced Under Different Conditions Using an X-ray Diffractometer - B.D. Igamov; A.I. Kamardin; D.Kh. Nabiev; G.T. Imanova; I.R. Bekpulatov; I.Kh. Turapov; N.E. Norbutaev (Қарағанды университетінің хабаршысы. Физика сериясы)
Mn4Si7 silicide crystals obtained by hot isostatic pressing (HIP) and diffusion methods were studied. As a result of the research, 11 peaks were identified in the Mn4Si7 crystal obtained by the HIP method, and 14 peaks in the Mn4Si7 crystal obtained by the diffusion method. The crystal size of Mn4Si7 silicide (DHIP) was established from 8.8∙10–9 m to 3.6∙10–8 m, (DDiff) from 6.2∙10–10 m to 9.1∙10–8 m. It has been established that the lattice tension between the atoms of the Mn4Si7 silicide crystal (εHIP) varies from 0.01 to 0.41, (εDiff) from 0.31 to 3.71. The dislocation density on the crystal surface (δHIP) turned out to be from 3.5∙1010 to 3.2∙1012, (δDiff) from 1∙1011 to 3.2∙1014. The degree of crystallization of Mn4Si7 silicide obtained by the (HIP) method is 7.02 %, the degree of amorphy is 92.98 %. It has been established that the Mn4Si7 silicide obtained by the diffusion method has a degree of crystallization of 9.3 % and a degree of amorphism of 90.7 %. (COD-1530134) (d). It has been established that the degree of crystallization of high-manganese silicide Mn4Si7 is low, and the degree of amorphy is high due to the fact that Mn and Si are bound in a non-stoichiometric state.